GEOMATH SEBAGAI APLIKASI PENGENALAN BAGUN DATAR BAGI SISWA SEKOLAH DASAR - Shinta Dwi Handayani; Ari Irawan (Prima Magistra: Jurnal Ilmiah Kependidikan, 2022)
The purpose of this research is to create an android-based application that can help students to more easily understand material related to flat shapes. Students are expected to be able to maximize the use of smartphones as a support for learning activities carried out. The method used in this research is research and development (RnD) with the ADDIE approach. There are two stages of adaptation carried out in this research, namely analysis of needs and analysis of curriculum. The media step is design, which is to design with the help of paint and make a storyboard of the application as well as a flowchart of the proposed running system. The third step is the development stage by entering data in android studio as software used in application development. The next step, namely implementation and evaluation, has not yet been carried out because currently research activities are still in the application development stage. The results of this research are in the form of application development that has been made by displaying several screen displays that will appear on Android. Currently, research activities are still in the validation stage by material and instructional media design experts.